Penerapan Strategi Pembelajaran Bamboo Dancing UntukMeningkatkan Motivasi Belajar Matematika Pada Siswa Kelas II SD Negeri 4 Karangsari Kabupaten Grobogan Tahun Ajaran 2014/ 2015 - Prihatin, Junia; , Ibu Dra. Risminawati, M.Pd (2016)
The purpose of this research is to improve students' motivation to learn Mathematics in grade II through the application of learning strategies Bamboo Dancing. Type of this research is the Classroom Action Research (CAR), which consists of planning, action, observation, and reflection using Bamboo Dancing learning strategies. This study uses two cycles with each cycle comprising 2 meeting. The subjects of this study are researchers who act as teachers and students of grade II SD Negeri 4 Karangsari totaling 20 students as subjects receiver action. The object of this study is a learning strategy Bamboo Dancing in increasing motivation to learn Mathematics in grade II SD Negeri 4 Karangsari Grobogan Academic Year 2014/2015. Methods of data collection is done through observation, interviews, and documentation. To ensure the validity of the data used source triangulation techniques and triangulation techniques. Data analysis techniques in this study consisted of: data collection, data reduction, data presentation, and conclusion. The results showed an increase in student motivation class II on the eyes learning of Mathematics in primary school 4 Karangsari. It can be seen from the students' motivation through several indicators, namely: Diligent face the task of pre-cycle by 49% in the first cycle increased to 58% and on the second cycle increased to 80%. Tenacious difficulties (not quickly despair) in the pre-cycle by 51%, in the first cycle increased to 60%, and the second cycle increased to 83%. Do not get bored of the task - a task that routine pre-cycle by 49%, in the first cycle increased to 55%, and the second cycle increased to 80%. Looking happy and memecahkn issues matter - matter of the pre-cycle by 52%, in the first cycle increased to 64%, and the second cycle increased to 80%.